2020
DOI: 10.1037/emo0000553
|View full text |Cite
|
Sign up to set email alerts
|

It’s about time: How integral affect increases impatience.

Abstract: Affect is integral to most decisions involving temptation. For instance, people may have difficulty saving for a house because they keep spending money on enjoyable, but more immediate items and events (e.g., fancy dinners). Little is known about how affect influences these types of intertemporal decisions. On the one hand, studies investigating the influence of incidental affect (i.e., affect that is unrelated to a decision, such as a person's mood) suggest that positive affect leads to increased impatience. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(91 reference statements)
3
5
0
Order By: Relevance
“…Similar to the findings of integral affect and other related studies (Geoffard and Luchini, 2010;Laube and van den Bos, 2020), the current research also found that after the priming of positive affect, individuals subjective time perception was longer. Moreover, in Study 2, we also revealed that incidental affect will also lead individuals to pay more attention to the delay attribute of IC.…”
Section: Mechanisms Underlying the Impact Of Incidental Affect In Impatient Choice: Time Perceptionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to the findings of integral affect and other related studies (Geoffard and Luchini, 2010;Laube and van den Bos, 2020), the current research also found that after the priming of positive affect, individuals subjective time perception was longer. Moreover, in Study 2, we also revealed that incidental affect will also lead individuals to pay more attention to the delay attribute of IC.…”
Section: Mechanisms Underlying the Impact Of Incidental Affect In Impatient Choice: Time Perceptionsupporting
confidence: 91%
“…To control for the impact of time perception differences on decision-making results, we integrated the subjective time estimate into the intertemporal decision model and replaced the time parameter t in the intertemporal decision model with the corresponding subjective time Perception T and estimated and compared the model parameters of the different participant conditions (Laube and van den Bos, 2020).…”
Section: Subjective Time Discountingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the temporal discounting variable per se, the current study expanded the range of intertemporal-related variables to two potential mediators proposed by LSH, i.e., future orientation and subjective future perception. This was built on the finding in previous studies that, even though temporal discounting preferences can remain unchanged, changes in indirect factors (e.g., subjective future perception) can still exert an influence to produce impatient decisions (Laube & van den Bos, 2020). In contrast to the above-mentioned null language effect on intertemporal decision, we identified a consistent strong-FTR L2 effect on weak-FTR L1 users' future orientation, as well as an unstable effect on their future perception.…”
Section: Including a Package Of Intertemporal-related Variablessupporting
confidence: 52%